Brake Clutch Assisted Engine Start Control for Series-parallel HEV - Wentai Zhou; Chen Wang; Jinrong Shan; Ji Gao; Dong Liu; Haisheng Yu; Tong Zhang (Jixie chuandong, 2019)
Aiming at the dynamic problem of interrupt in the starting process of hybrid vehicle， a new scheme of starting engine with brake assist is presented. The control strategies of brake clamping torque control and torque coordination are designed， the simulation analysis and test verification are carried out. The test results show that the dynamic performance of engine start process is improved obviously. The result shows that the brake clutch assited scheme is reasonable， the control strategy is practicable.